2009
DOI: 10.1002/pbc.22086
|View full text |Cite
|
Sign up to set email alerts
|

Pegfilgrastim for prevention of chemotherapy‐associated neutropenia in pediatric patients with solid tumors

Abstract: Pegfilgrastim following dose intensive chemotherapy for solid tumors is feasible in children, including those <45 kg. The frequency and duration of severe neutropenia, as well as incidence of febrile neutropenia, were similar to filgrastim historic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…21 In this study, FN incidence in Mexican pediatric patients was consistent with this observation. The SIOPEL-4 study, which evaluated the efficacy and safety of dose-dense CDDPBC in children with high-risk hepatoblastoma, found incidence of FN of 71%.…”
Section: Discussionsupporting
confidence: 90%
“…21 In this study, FN incidence in Mexican pediatric patients was consistent with this observation. The SIOPEL-4 study, which evaluated the efficacy and safety of dose-dense CDDPBC in children with high-risk hepatoblastoma, found incidence of FN of 71%.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the analysis of costs in 2 randomized trials, one single-centre, double-blind, placebo-controlled, and one multicenter, open-label, showed that the use of pegfilgrastim was less expensive than filgrastim [22],[23]. Pegfilgrastim is still off-label for pediatric patients despite several authors having documented its efficacy and safety for prophylaxis of febrile neutropenia post-chemotherapy and as the mobilizing agent for peripheral blood stem cell collection [6][10],[12][15],[34]. No data have been published so far on the role of pegfilgrastim as a supportive agent after pediatric autologous HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Pegfilgrastim was administered subcutaneously as a single injection of 100 µg/kg, up to a maximum of 6 mg, on Day +3 after the end of chemotherapy. The dose of 100 µg/kg of pegfilgrastim was chosen by reference to published pediatric experience 12‐19 . Blood count was checked every 2 to 3 days until the nadir of white blood cells (WBCs) was reached and then every 1 to 2 days until PBSC collection by leukapheresis.…”
Section: Methodsmentioning
confidence: 99%
“…Pegfilgrastim is not licensed for pediatric use, but several retrospective and prospective Phase II to III, single‐center studies have recently shown that its efficacy and safety in reducing severe neutropenia after chemotherapy is comparable to filgrastim 12‐18 . Limited data are available on the use of pegfilgrastim in pediatric patients as a mobilizing agent in association with chemotherapy, the studies being mainly single‐center experience and differing in the dose and mobilization schemes used 19‐21 .…”
mentioning
confidence: 99%